Importance of the Second Homes in the Context of Weekend Trips Preferred by Canadian Polish People - Kamila ZIÓŁKOWSKA-WEISS (Communications of International Proceedings, 2021)
Canada is diverse taking into account natural and cultural factors, offering conditions to practise all forms of leisure, cognitive, cultural and qualified tourism. Tourism is developing mainly due to high internal demand and in connection with numerous economic sectors in this vast area. The urban complexes with millions of inhabitants in Canada, such as Toronto and Vancouver constituting the major sources of tourism demand, have a decisive impact on its development. The objective of this article is to present the results of the survey among 1186 respondents living in the Greater Toronto Area which includes the provinces of: Halton, Peel, York, Durham and the City of Toronto itself. The research shows that short-term trips, the so-called weekend trips, within the territory of Canada constitute the most desired trips per year among the respondents. The types of tourist activities during the above-mentioned trips as well as spatial destinations of the weekend trips among the Polonia living in the Greater Toronto Area will be discussed. Particular attention will be paid to their ownership of the second homes (holiday cottages) in which they rest on the outskirts of the crowded Toronto during the short-term trips.
Keywords: Polish people; Toronto; tourism; second home